THE INTENDED USE OF FUNDS AND IPOs MARKET PERFORMANCE IN INDONESIAN CAPITAL MARKET - Harlina Meidiaswati; Nugroho Sasikirono; Dina Novita (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2019)
Specific information on the IPO prospectus can affect the stock's market performance, both the initial returns and the long-term performance. The disclosure of the purpose of IPO proceeds to: acquisition, investment, group financing, debt repayment and working capital, as a specific form of information is indicated to affect both initial return and long-term stock returns. We conducted a test of 148 IPOs on the Indonesia Stock Exchange in the period 2006–2013. Data analysis was performed using OLS and probit regression. The test results show that there is a negative relationship between the intention of the acquisition and debt repayment with underpricing. The results also show that IPOs with the purpose of the debt repayment is positively related to the long-term market performance. The age of the company has a negative effect on IPOs with the purpose of acquisition and debt repayment, while the size of the company proxied by total assets is positively related to the intentions of group financing and debt repayment